AN ANALYSIS OF SWEAR-WORDS USED IN PONDOK TINGGI DIALECT OF KERINCI LANGUAGE - Eliza Trimadona (Lembaga Penelitian dan Pengabdian pada Masyarakat, Institut Agama Islam Negeri (IAIN) Kerinci, Jambi, 2016)
The expression of feelings can be delivered politely or impolitely. The impolite expression usually delivered by using swearwords or obscenities. In English, it is well-known as swear words. This study aimed to describe the types, meaning, and function of swear words spoken by natives in PondokTinggi, Sungai Penuh city. The research that was conducted inPondokTinggi, was included into descriptive study where the facts are what exactly found related to those words.From the results of the study, researchers found six different types of swear words that grouped by type that came from the name of the animal, excretion, parts and body functions, the plant names, name of the devil and sex. From this study, the meaning and the function of swear words based on the context of the situation of swear words seen from expression of native speakers.As this research can be still developed, it is advisable for other researchers to be able to produce advanced research for a deeper findings.